Continuation Electroconvulsive Therapy for Patients With Clozapine-Resistant Schizophrenia: A Pilot Study. Issue 3 (September 2019) - Braga, Raphael J.; John, Majnu; Schooler, Nina R.; Bailine, Samuel H.; Malur, Chitra; Mendelowitz, Alan; Petrides, Georgios
Abstract : Objectives: The risk of relapse after a successful acute course of treatment is a clinical challenge in electroconvulsive therapy (ECT) practice, particularly in patients with a history of marked resistance to previous treatments. Research suggests that a gradual decrease of ECT or its long-term continuation might be the best strategy. Notwithstanding, current studies do not address the role of continuation ECT in the truly refractory cases, that is, the clozapine-resistant patients. Our group published a randomized controlled trial of ECT augmentation of clozapine in clozapine-resistant patients with schizophrenia, where the augmentation was vastly superior in efficacy for the acute treatment. The aim of the current study is to evaluate the efficacy of continuation ECT for patients who showed response to the combination of acute ECT and clozapine for treatment-resistant schizophrenia. Methods: Continuation ECT was offered to all patients who completed the acute study and who met response criterion. We followed a tapered schedule of 4 weekly ECT sessions, followed by 4 ECT sessions every 2 weeks and 2 monthly ECT sessions for a total of 10 sessions. Results: Patients sustained the gains achieved with the acute course of ECT, and no individual patient presented with clinically relevant worsening of symptoms. Moreover, the long-term use of ECT was not associated with added adverse effects. Conclusions: This is an open pilot study with a small sample size, and results should be interpreted accordingly, but this report offers a relevant starting point for much needed future studies.